БЮДЖЕТНИЙ КОНТРОЛЬ ПРИ ПЛАНУВАННІ МІСЦЕВИХ БЮДЖЕТІВ - Кириленко, Ольга Павлівна; Вацлавський, Олег Іванович (Науковий журнал «Світ фінансів», 2019)
Кириленко О. П., Вацлавський О. І. Бюджетний контроль при плануванні місцевих бюджетів.Досліджено практику здійснення бюджетного контролю в процесі складання, розгляду і прийняття рішень про місцеві бюджети. Проведено аналіз динаміки прогнозних і затверджених показників доходів та видатків місцевих бюджетів України. Визначено основні проблеми планування доходів і видатків місцевих бюджетів. Обґрунтовано доцільність функціонування громадського контролю в процесі формування місцевих бюджетів. Виокремлено напрями удосконалення бюджетного контролю при складанні, розгляді та прийнятті рішень про місцеві бюджети. Кириленко О. П., Вацлавский О. И. Бюджетный контроль при планировании местных бюджетов.Исследовано практику осуществления бюджетного контроля в процессе составления, рассмотрения и принятия решений о местных бюджетах. Проведен анализ динамики прогнозных и утвержденных показателей доходов и расходов местных бюджетов Украины. Определены основные проблемы планирования доходов и расходов местных бюджетов. Обоснована целесообразность функционирования общественного контроля в процессе формирования местных бюджетов. Выделены направления совершенствования бюджетного контроля при составлении, рассмотрении и принятии решений о местных бюджетах. Kyrylenko O., Vatslavskyi O. Budget control when planning local budgets.Introduction. Most of the local budgets are subsidized, there are many shortcomings in planning the revenue and expenditure part of the budgets, a rather high level of violations when considering and taking decisions on local budgets, which, accordingly, does not carry out a number of socio-economic functions of local self-government bodies. Therefore, the key role in reducing all of the above-mentioned negative phenomena, which are currently present in the process of forming local budgets, is allocated to budget control.Purpose. The purpose of the article is to analyze the current state of budget control in drafting, reviewing and making decisions about local budgets in order to identify the most significant problems and outline ways of their solution taking into account therealities of the modern economy.Results.To date, there are many shortcomings in the planning of the revenue and expenditure part of the budgets, as well as a rather high level of violations when considering and making decisions about local budgets, due to which the number of socioeconomic functions of local self-government bodies is not carried out accordingly. In 2017, at the time of the inspection, the facts of conducting operations with allocation of budget funds for the total amount of UAH 99.4 million were detected in violation of the legislation, which is UAH 20.9 million. more than in the previous year, incl. Violation of funds from the state budget – 58.6 million UAH, with funds from local budgets – more than 40.8 million UAH. A key role in reducing all of the above-mentioned negative phenomena, which are currently present in the process of formation of local budgets, is allocated to budget control.Conclusions. The conducted research of the practice of budget control in drafting, reviewing and taking decisions on local budgets made it possible to formulate the following conclusions and proposals: it is necessary to form a single mechanism for calculating the planned and forecast indicators of revenues of local budgets; it is necessary to increase the level of openness and transparency in the process of drafting local budgets; it is worth improving the legislative framework that would oblige local authorities to involve public representatives in the process of preparing and adopting decisions on local budgets.